2020
DOI: 10.1002/ana.25937
|View full text |Cite
|
Sign up to set email alerts
|

Association between Migraine and Cryptogenic Ischemic Stroke in Young Adults

Abstract: Objective To assess the association between migraine and cryptogenic ischemic stroke (CIS) in young adults, with subgroup analyses stratified by sex and presence of patent foramen ovale (PFO). Methods We prospectively enrolled 347 consecutive patients aged 18 to 49 years with a recent CIS and 347 age‐ and sex‐matched (±5 years) stroke‐free controls. Any migraine and migraine with (MA) and migraine without aura (MO) were identified by a screener, which we validated against a headache neurologist. We used condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…3.6 in men in the most recent study published in 2020). 26 There may also be an increased risk for hemorrhagic stroke in patients with migraine, however. A large study published in 2013 27 found an increased risk (adjusted H.R.…”
Section: Discussionmentioning
confidence: 99%
“…3.6 in men in the most recent study published in 2020). 26 There may also be an increased risk for hemorrhagic stroke in patients with migraine, however. A large study published in 2013 27 found an increased risk (adjusted H.R.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on stroke etiology reported lower frequencies of large vessel and cardio-embolic stroke etiology in female migraine patients and more infarcts of unknown origin in migraine patients in general ( Rist et al, 2010 ; Li et al, 2015 ). In a recent study, migraine with aura was strongly associated with cryptogenic stroke, whereas such association was not found in migraine without aura ( Martinez-Majander et al, 2021 ). The association of migraine with aura with stroke was independent of vascular risk factors or patent foramen ovale.…”
Section: Discussionmentioning
confidence: 95%
“…The study design was described in detail previously. 18,19 Participants for the present analysis were enrolled between October 2013 and April 2020. Written informed consent was obtained from all participants, and the study was approved by the ethics committees of the participating hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Based on medical records and structured interviews, we identified relevant comorbidities, such as diabetes mellitus (i.e., prior diabetes diagnosis and/or prior antidiabetic medication), hypertension (i.e., prior hypertension diagnosis, prior antihypertensive medication, or the mean of two office blood pressure measures >140/90 mmHg at study visit), history of cardiovascular disease (coronary heart disease, congestive heart failure, peripheral arterial disease, or atrial fibrillation), and migraine with aura (MA), assessed with a validated migraine screening protocol. 19 Information on lifestyle factors was based on structured interviews conducted during study visits. Cigarette smoking was classified as smoking at least one cigarette during the year prior to the index stroke.…”
Section: Comorbiditiesmentioning
confidence: 99%